A Hybrid Energy Management System for Reliable and Sustainable Microgrid Performance - Palaloi, Sudirman; Prastawa, Andhika; Soeprijanto, Adi (Engineering, Technology & Applied Science Research, 2025)
This study develops a hybrid Energy Management System (EMS) that includes the primary grid power, a 10 kVA diesel generator, a 40 kW solar system, a 30 kW wind turbine, and a 66.6 kWh battery for optimal utilization of renewable energy and minimal utilization of fossil fuel. The introduced approach employs a fuzzy logic-based control technique, which is particularly proposed to negate the uncertainties, nonlinearity, and fluctuation characteristics in the renewable energy generation sources. Dynamic switching logic is created to tune the system response according to the operating modes, off-grid or on-grid, to maintain stability and performance under different conditions. The system is modeled and simulated in the MATLAB/Simulink environment. Three cases are simulated: static off-grid operation at a constant 50 kW load, static on-grid operation at a 200-kW load, and dynamic variations in solar irradiance between 0 and 1,000 W/m² and wind speed between 0 and 12 m/s. The results demonstrate the system's capacity to undergo seamless transitions between energy sources, ensure a continuous power supply, achieve more than 90% energy efficiency, and achieve an average renewable energy contribution of 65% for dynamic loads. The transition from off-grid to on-grid mode occurs within a period of 1 s without imposing a great load disturbance. The battery shows adaptive charging and discharging behavior for adapting to environmental changes in support of system robustness. The current study confirms the effectiveness of fuzzy logic as an intelligent and adaptive control technology for hybrid microgrid EMS, and it serves as a valuable reference for the application of sustainable energy in rural and remote areas.